Immunohistochemical Detection of Enteropathogens Associated with Calf Diarrhea - Suresh, Raksha; Brar, Apminder Pal Singh; Leishangthem, Geeta Devi; Sandhu, Bhupinder Singh (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The objective of the study was to determine the infectious agents responsible for causing diarrhea in neonatal calves throughimmunohistochemistry. One hundred intestinal samples of dead calves with a history of diarrhea were collected from farms in and aroundLudhiana and the postmortem hall of the Department of Veterinary Pathology, GADVASU, Ludhiana. All the samples were subjectedto routine histopathology. Immunohistochemistry was employed to detect the presence of etiological agents in all of these samples.The primary gross lesions observed in the intestine were congestion, catarrhal enteritis, and fibrin on the mucosal surface. Commonhistopathologic observations were necrotic enteritis along with massive infiltration of mononuclear cells. 54 samples were found tobe positive for Salmonella spp., 50 for Clostridium perfringens, 8 for Cryptosporidium spp., 4 for E. coli (K99), 4 for rotavirus. Eimeria spp.was also detected in 5 samples through immunohistochemistry. A total of 38 samples showed the involvement of multiple agents. Thestudy concludes that calf diarrhea can be caused by multiple infectious etiological agents, either single or multiple, and that Clostridiumperfringens and Salmonella spp were the main etiological agents responsible for causing diarrhea. Immunohistochemistry was foundto be an effective tool for detecting the various etiological agents of calf diarrhea.
Keywords: Clostridium perfringen; Histopathology; Immunohistochemistry; Neonatal calf diarrhea; Salmonella spp